1982
DOI: 10.1126/science.7079745
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Nocturnal Plasma Melatonin Peak in Patients with Estrogen Receptor Positive Breast Cancer

Abstract: Plasma melatonin concentrations were determined over a period of 24 hours in 20 women with clinical stage I or II breast cancer. In ten of the patients, whose tumors were estrogen receptor positive, the nocturnal increase in plasma melatonin was much lower than that observed in eight control subjects. Women with the lowest peak concentration of melatonin had tumors with the highest concentrations of estrogen receptors. A significant correlation was found between the peak plasma melatonin concentration and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
0
2

Year Published

1986
1986
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(81 citation statements)
references
References 9 publications
3
76
0
2
Order By: Relevance
“…Women with the lowest peak concentration of melatonin had tumors with the highest concentrations of estrogen receptors. A significant correlation was found between the peak plasma melatonin concentration and the tumor estrogen receptor concentration in 19 of the patients [218] Normal individuals, women with breast cancer, and women at high risk for breast cancer…”
Section: Genomic Stabilitymentioning
confidence: 92%
“…Women with the lowest peak concentration of melatonin had tumors with the highest concentrations of estrogen receptors. A significant correlation was found between the peak plasma melatonin concentration and the tumor estrogen receptor concentration in 19 of the patients [218] Normal individuals, women with breast cancer, and women at high risk for breast cancer…”
Section: Genomic Stabilitymentioning
confidence: 92%
“…These authors suggested that a decrease in pineal function, whatever its cause, and the consequent reduction in melatonin secretion, could induce a state of relative hyperestrogenism, and the early and prolonged exposure of the breast tissue to the estrogens could be involved in the etiology of the breast tumor. A few years later, Tamarkin et al (1982), in an article in Science, described a relationship between plasma melatonin concentration and breast cancer. Women with estrogen receptor (ER)-positive breast adenocarcinomas had nocturnal plasmatic concentrations of melatonin significantly lower than healthy women or women suffering ER-negative breast tumors.…”
Section: The Hypothesis On the Role Of The Pineal Gland And Melatoninmentioning
confidence: 99%
“…Raiklin с соавт. выявили повышение уровня МЛТ у больных неза-висимо от локализации опухолевого процесса [32] и, на-против, низкий уровень МЛТ в моче у больных РМЖ [33], а также снижение ночных пиковых концентраций в кро-ви при гормонпозитивном РМЖ [34]. В исследовании Lissoni P. сравнивались концентрации МЛТ у пациентов со злокачественными новообразованиями (n=64) и здоро-вых добровольцев (n=52).…”
unclassified